FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS BANK PERKREDITAN RAKYAT - Pertiwi, Ni Putu Julia; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2015)
This study aimed to determine the effect of credit turnover rate , cash turnover rate, and the growth in the number of credit customers to profitability at BPR in Gianyar 2010-2012. This research was done by using multiple linear regression analysis techniques. The number of samples obtained by using purposive sampling method is as much as 15 B PR . The result of the analysis get credit t urnover rate and growth of the amount of credit customers partially positive effect on profitability at BPR in Gianyar Regency period 2010-2012 while the cash turnover is not partial effect on the profitability of the BPR in Gianyar 2010-2012. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Profitability; Credit Turnover; Cash Turnover; Growth Credit Customer Numbers